2017
DOI: 10.3389/fvets.2017.00096
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Antimicrobial Resistance Phenotypes in Salmonella Isolated from Commercial Poultry Farms

Abstract: Salmonella remains the leading cause of foodborne illness in the United States, and the dissemination of drug-resistant Salmonellae through the food chain has important implications for treatment failure of salmonellosis. We investigated the ecology of Salmonella in integrated broiler production in order to understand the flow of antibiotic susceptible and resistant strains within this system. Data were analyzed from a retrospective study focused on antimicrobial resistant Salmonella recovered from commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 46 publications
3
37
0
3
Order By: Relevance
“…Highest resistance was observed to; Trimethoprim-sulphurmethoxazole, Tetracycline, Ampicillin and Nitrofurantoin: these have been documented as the most commonly used antimicrobial agents in the agricultural sector in Uganda [21]. These finding are consistent with studies done elsewhere on similar isolates whose source was animals [22]. In addition, these studies also reported a possible transmission of the resistance in these isolates to humans.…”
Section: Discussionsupporting
confidence: 84%
“…Highest resistance was observed to; Trimethoprim-sulphurmethoxazole, Tetracycline, Ampicillin and Nitrofurantoin: these have been documented as the most commonly used antimicrobial agents in the agricultural sector in Uganda [21]. These finding are consistent with studies done elsewhere on similar isolates whose source was animals [22]. In addition, these studies also reported a possible transmission of the resistance in these isolates to humans.…”
Section: Discussionsupporting
confidence: 84%
“…In nontyphoidal Salmonella serotypes as a whole, NARMS found 11.2% of isolates resistant to streptomycin and 10.4% resistant to tetracyclines (CDC, ). Streptomycin resistance is thought to be linked with numerous resistance genes, which may explain why our isolates demonstrated phenotypic resistance to streptomycin yet a known gene encoding this resistance was not identified (Liljebjelke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As most Salmonella infections are associated with consumption of meats, milk, and eggs, the veterinary use of antimicrobials, especially those important for treatment of humans, has long been a contentious issue (Cox and Ricci, 1969). While there is epidemiological data to support the link between antimicrobial use and resistance (Bortolaia et al, 2015;Noyes et al, 2016;Andersen et al, 2017;Caffrey et al, 2017;Shigemura et al, 2018), it is generally difficult to ascertain causal effect depending on the antimicrobial (Fairchild et al, 2005;Smith et al, 2007;Agga et al, 2016), food animal (Agga et al, 2016), level or scope of food animal production system (Idris et al, 2006;Andersen et al, 2017;Liljebjelke et al, 2017), or method of quantifying resistance (Fairchild et al, 2005;Smith et al, 2007;Agga et al, 2016). In poultry production, the antimicrobials available for use in the US are limited to 15 drugs (Singer and Hofacre, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood that any of these antimicrobials are used are mostly dependent on economics, weighing the cost of the drug against the level of disease (Singer and Hofacre, 2006). A commercial poultry farm may go a full year without any therapeutic antimicrobial use (Liljebjelke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation